Association between pubertal status and body fat percentage among Malay adolescents in Kuala Nerus, Terengganu - Nur Afifah Mohd Khair; Bee, Suan Wee (Penerbit Universiti Kebangsaan Malaysia, 2021)
Body composition is defined as the proportion of fat (FM) and fat-free mass (FFM) in our body. It is an important aspect of both individual’s and populations’ health. The rising prevalence of obesity among adolescents has highlighted the significance of body fat measurement and the factors that influence it. Therefore, this study aims to measure the body fat percentage (BF%) by using bioelectrical impedance analysis (BIA) and to observe its association with pubertal status among Malay adolescents in Kuala Nerus, Terengganu. Adolescents from 10 to 16 years old were the subject of this crosssectional study. Weight, height, and waist circumference were measured anthropometrically, and body composition was determined using Bodystat Quadscan 4000 through BIA procedures. Questionnaires consist of socio-demographic characteristics and Tanner staging for the determination of pubertal status. A total of 310 students participated in this study (female, n=165, male n=145). The percentage of overweight and obese adolescents in Kuala Nerus was 12.9% and 10.6%, respectively. The difference in BF% between genders was significant (p<0.001), with pubertal girls having a greater BF% than boys (28.05±7.31% vs 17.20±8.43%). Between pubertal status and BF%, there was a significant difference (p<0.05). However, there was no significant association between BF% and pubertal status. Gender and pubertal status have an impact on the BF%. Thus, pubertal status should be considered when measuring BF% because it varies by individual and gender.